PENGARUH PEMBELAJARAN DALAM DARINGAN (DARING) TERHADAP MINAT BELAJAR MAHASISWA FAKULTAS EKONOMI PRODI MANAJEMEN UNIVERSITAS SISINGAMANGARAJA XII TAPANULI TAHUN AJARAN 2020/2021 - Santiria Eska Lestari Manik; Herta Manurung; Hotlin Siregar; Leonard R Sinaga (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2021)
This study aims to determine the effect of online learning on students' interest in learning from the economics faculty of the management study program at Sisingamangaraja XII Tapanuli University in the 2020/2021 academic year.The population in this study were all students of the Economics Faculty of Stambuk 2016-2020, and the sample was 79 respondents, using the